Continuous Synthesis of Biodiesel from Outstanding Kernel Oil in a Packed Bed Reactor Using Burkholderia cepacia Lipase Immobilized on Magnetic Nanosupport - Bento, Heitor B. S. [UNESP]; Reis, Cristiano E. R.; Pinto, Pedro A.; Cortez, Daniela V.; Vilas Bôas, Renata N.; Costa-Silva, Tales A.; Carvalho, Ana K. F.; de Castro, Heizir F. (Springer Nature, 2021)
This study deals with the use of commercial lipase stabilized onto magnetic particles of iron oxides (Fe3O4/γ-Fe2O3) and applied as a heterogeneous biocatalyst in the synthesis of ethyl esters (biodiesel) in a solvent-free medium on a continuous process. Magnetic particles were synthesized by alkaline co-precipitation, silanized, activated and subsequently used for immobilization of Burkholderia cepacia lipase. The results regarding the lipase immobilization showed an enzyme activity retention of about 53% and an increase in the KM value in about threefold (from 410 to 1262 mmol L−1) and a decrease in the Vmax value in sevenfold (From 12,390 to 1786 U g−1) when compared with the free enzyme. The immobilization process favored the thermal stability and increased the half-time of the enzyme about tenfold at 50 °C. The immobilized derivative was evaluated to aroma production and the activity of esterification was calculated as being 56.7 μmol L−1 g−1 min−1, which corresponds to a productivity value of 0.58 g ester L−1 h−1. The immobilized system was also used to mediate transesterification of kernel oil in a fixed bed reactor operating in a continuous flow with a reaction medium composed of oil and ethanol at a molar ratio of 1:12, 50 °C and space–time of 16 h. The operational stability of the immobilized lipase estimated at 47 days allowed to operate the reactor with high productivity of 38.7 ± 0.7 mg g−1 h−1. Also, the product properties of the ester content (> 96.5%) and kinematic viscosity value (5.32 ± 0.4 mm2 s−1 at 40 °C) meet the requirements of the ANP and ASTM (D6751) for biodiesel fuel. Graphic Abstract: [Figure not available: see fulltext.]
Keywords: Biodiesel; Continuous reaction; Enzyme immobilization; Lipase; Magnetic nanoparticles